Direct Synthesis of Multi-layer MoS\(_2\) Nanodots by Chemical Vapor Deposition - Anh Vuong, Vy; Manh Hung, Chu (Communications in Physics, 2018)
The current work reports a direct synthesis of multi-layer MoS2 nanodots by a chemical vapor deposition method. The morphological, structural and optical properties of the growing MoS2 are investigated by field emission scanning electron microscopy (FESEM), Raman and Photoluminescence (PL) spectroscopy, respectively. High magnification FESEM image reveals a layer of MoS2 nanodots with the average size of about 10 nm. Resonance Raman data exhibits the two active E12g and A1g modes corresponding to in-plane variation of Mo and S atoms centered at 383.3 cm-1 and to out of plane variation of S atoms located at 407.1 cm-1, respectively. The spacing between two peaks is about 23.8 cm-1, which can be used to evaluate the number of MoS2 layer. The Raman spectrum also indicates any intensity enhancement of the A1g peak compared to the E12g peak. This result is elucidated through the quantum confinement effect. The PL emission shows a pronounced peak at 505 nm that is significant blue shift compared to single MoS2 layer. The interpretation of this phenomena is discussed in detail.